In Vivo Penetrating Microelectrodes for Brain Electrophysiology - Alexander Erofeev; Ivan Antifeev; Anastasia Bolshakova; Ilya Bezprozvanny; Olga Vlasova (Sensors, 2022)
In recent decades, microelectrodes have been widely used in neuroscience to understand the mechanisms behind brain functions, as well as the relationship between neural activity and behavior, perception and cognition. However, the recording of neuronal activity over a long period of time is limited for various reasons. In this review, we briefly consider the types of penetrating chronic microelectrodes, as well as the conductive and insulating materials for microelectrode manufacturing. Additionally, we consider the effects of penetrating microelectrode implantation on brain tissue. In conclusion, we review recent advances in the field of in vivo microelectrodes.